Effects of training with a dynamic moment of inertia bat on swing performance - Liu, C.; Liu, Y. -C.; Kao, Y. -C.; Shiang, T. Y. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to investigate the effects of the 8-week dynamic moment of inertia (DMOI) bat training on swing velocity, batted-ball speed, hitting distance, muscle power, and grip force. The DMOI bat is characterized in that the bat could be swung more easily by reducing the moment of inertia at the initial stage of swing without decreasing the bat weight and has a faster swing velocity and lower muscle activity. Seventeen varsity baseball players were randomly assigned to the DMOI bat training group (n = 9) and the normal bat training group (n = 8). The training protocol was 7 swings each set, 5-8 sets each time, 3 times each week, and 8 weeks' training period. The results showed that the swing training with the DMOI bat for 8 weeks significantly increased swing velocity by about 6.20% (96.86 ± 8.48 vs. 102.82 ± 9.93 km/h), hitting distance by about 6.69% (80.06 ± 9.16 vs. 84.99 ± 7.26 m), muscle power of the right arm by about 12.04% (3.34 ± 0.41 vs. 3.74 ± 0.61 m), and muscle power of the left arm by about 8.23% (3.36 ± 0.46 vs. 3.61 ± 0.39 m) (p < 0.05). Furthermore, the DMOI bat training group had a significantly better change percentage in swing velocity, hitting distance, and grip force of the left hand than did the normal bat training group (p < 0.05). The findings suggested that the swing training with the DMOI bat has a positive benefit on swing performance and that the DMOI bat could be used as a new training tool in baseball.